Pháp ché̂ là gì? - Vũ Đức Chiêu (Vietnamese law coll. (Harvard Law School), 1974)
A popular work on law, legal institutions in socialist countries and the Democratic Republic of Vietnam (legal system, rights and duties of citizens)